Improving the Quality of Academic Work of Master’s Students in Educational Management at Universitas Negeri Jakarta Based on Online Workshops - Syam, Aldo Redho; Listyasari, Winda Dewi; Sari, Cynthia Mayang; Mayasari, Linda Ika; Ahmad, Iqbal Faza (Universitas Darunnajah, Jakarta, Indonesia, 2025)
This community service activity originates from the ongoing challenges faced by higher education institutions in improving the quality of academic writing, particularly theses, which is highly relevant in the Master's Program in Educational Management at Universitas Negeri Jakarta (UNJ), where students often struggle with critical thinking and the application of appropriate methodologies. The objective of this activity is to enhance students' academic writing skills through an online workshop focused on thesis preparation, covering aspects such as research methodology, data analysis, and structured academic writing. The workshop, held on August 4, 2025, via Zoom Meeting, was attended by 76 active students and featured three experts in the field of educational research who presented material on research frameworks, methodologies, and academic writing techniques. The methods used included synchronous presentations, interactive Q&A sessions, and group discussions facilitated by a moderator. The findings indicate that the workshop significantly improved students' cognitive, affective, and psychomotor competencies in thesis writing, with active participation and direct interaction with the speakers boosting students' confidence and problem-solving skills. However, technical challenges, such as unstable internet connections, presented barriers. Factors influencing the workshop's effectiveness include speaker competence, student engagement, peer collaboration, technological readiness, and institutional support. The implications of this workshop emphasize the importance of ongoing technical training for both students and lecturers, improvements in digital infrastructure, and continuous mentoring to maintain the quality of academic writing. This model can be further developed into a structured support system for thesis writing in similar academic environments.